2011
DOI: 10.2134/jeq2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

Levels, Distribution, and Health Risk of Phthalate Esters in Urban Soils of Beijing, China

Abstract: The content of phthalate esters (PAEs) was investigated in urban soil samples ( = 127, 0-20 cm) collected from a business area (BU), classical garden (CL), culture and educational area (CU), large public green space (LA), residential area (RE), and roadside area (RO) in Beijing. The sum of all PAE contents ranged from 1.9 to 3141.7 ng/g, with an average of 1139.6 ± 727.6 ng/g. Di-n-butyl phthalate (DBP) and di-(2-ethylhexyl) phthalate (DEHP) were the major contaminants in the soil samples. The content of DEHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 24 publications
4
40
1
1
Order By: Relevance
“…For example, the phthalic acid ester concentrations in urban soils were found to be higher than those in rural soils, which was due to the intense commercial activities and greater phthalic acid ester discharge from plastic materials in urban regions than rural regions (Sun et al 2013;Xia et al 2011b). Furthermore, transverse phthalic acid ester distribution was also impacted by the phthalic acid ester mobility in the soil (Liu et al , 2010b; for example, elevated concentrations of diethylhexyl phthalate and dibutyl phthalate were found at a further distance rather than at the disposal center ).…”
Section: Transverse Distribution Of Phthalic Acid Esters In Soilmentioning
confidence: 99%
“…For example, the phthalic acid ester concentrations in urban soils were found to be higher than those in rural soils, which was due to the intense commercial activities and greater phthalic acid ester discharge from plastic materials in urban regions than rural regions (Sun et al 2013;Xia et al 2011b). Furthermore, transverse phthalic acid ester distribution was also impacted by the phthalic acid ester mobility in the soil (Liu et al , 2010b; for example, elevated concentrations of diethylhexyl phthalate and dibutyl phthalate were found at a further distance rather than at the disposal center ).…”
Section: Transverse Distribution Of Phthalic Acid Esters In Soilmentioning
confidence: 99%
“…They are widely used in general plastic products, cosmetics, personal care products, food packaging and medical products (Van Wezel et al, 2000;Hens and Caballos, 2003;Cai et al, 2008;Xia et al, 2011). The global consumption of PAEs is about 6.0 million tons per annum (Xie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that agricultural soils and vegetables have been contaminated by toxic pollutants (Gao et al, 2005). Some investigators have found that toxic pollutants such as heavy metals (Hu and Ding, 2009), polycyclic aromatic hydrocarbons (PAHs) (Yin et al, 2008), persistent organic pollutants (POPs) (Gao et al, 2005), organochlorine pesticides (Tao et al, 2005) and PAEs are present in suburban agricultural soils (Chen et al, 2011;Xia et al, 2011;Kong et al, 2012). PAEs are among the most abundant semi-volatile organic chemicals found in Chinese soils .…”
Section: Introductionmentioning
confidence: 99%
“…Phthalates are not chemically but only physically bound to the polymer chains; hence, they may be leached into the environment and are ubiquitously found in air, water, soils, and sediments [13][14][15][16][17]. People exposure to PAEs may arise from toys, child-care articles, building materials, home furnishing, car interiors, clothing, medical devices, and foodcontact materials.…”
Section: Introductionmentioning
confidence: 99%